#### Answer

The value of $\left( g\circ f \right)\left( 0 \right)$ is $-6$.

#### Work Step by Step

The composition of f with g can be defined as the function $\left( f\circ g \right)$ and $\left( f\circ g \right)\left( x \right)$ which is equivalent to $f\left( g\left( x \right) \right)$.
Consider,
$\left( g\circ f \right)\left( 0 \right)=g\left( f\left( 0 \right) \right)$
Here,
$f\left( 0 \right)=2$.
Then,
$g\left( f\left( 0 \right) \right)=g\left( 2 \right)$
And value of $g\left( 2 \right)=-6$.
Therefore, $\left( g\circ f \right)\left( 0 \right)=-6$
Hence, the value of $\left( g\circ f \right)\left( 0 \right)$ is $-6$.